2017
DOI: 10.1051/0004-6361/201629603
|View full text |Cite
|
Sign up to set email alerts
|

The optical counterpart to the Be/X-ray binary SAX J2239.3+6116

Abstract: Context. Be/X-ray binaries represent the main group of high-mass X-ray binaries. The determination of the astrophysical parameters of the counterparts of these high-energy sources is important for the study of X-ray binary populations in our Galaxy. X-ray observations suggest that SAX J2239.3+6116 is a Be/X-ray binary. However, little is known about the astrophysical parameters of its massive companion. Aims. The main goal of this work is to perform a detailed study of the optical variability of the Be/X-ray b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The optical counterpart is a V = 14.8 B0Ve star located at a distance of ∼4.9 kpc (in't Zand et al 2000). The long-term optical variability is characterized by the slow dissipation of the circumstellar disk around the Be star companion (Reig et al 2017). SAX J2239.3+6116 was observed during four contiguous nights from the Skinakas observatory on 22-25 August 2011 and20-23 August 2019 (Table D.3).…”
Section: Cep X-4mentioning
confidence: 99%
See 1 more Smart Citation
“…The optical counterpart is a V = 14.8 B0Ve star located at a distance of ∼4.9 kpc (in't Zand et al 2000). The long-term optical variability is characterized by the slow dissipation of the circumstellar disk around the Be star companion (Reig et al 2017). SAX J2239.3+6116 was observed during four contiguous nights from the Skinakas observatory on 22-25 August 2011 and20-23 August 2019 (Table D.3).…”
Section: Cep X-4mentioning
confidence: 99%
“…To investigate whether the nature of the BeXB variability is similar or not to that of classical Be stars, we compared our results of the previous sections with those obtained by Labadie- Bartz et al (2022) for a larger sample of Be stars observed by TESS during the first year of the mission. In this comparison, we take into account that the spectral type distribution in BeXB lies in the narrow range O9-B2, with a peak around B0 (Negueruela 1998;Reig et al 2017), and hence we compare our results with those of the early group (B3 and earlier) defined by Labadie- Bartz et al (2022).…”
Section: Comparison With B and Classical Be Starsmentioning
confidence: 99%
“…Some papers greatly facilitated the process as they already listed information on some HMXBs in our catalogue. Orbital periods, spin periods, and spectral types are found in Belczynski & Ziolkowski (2009), spin periods of pulsars are reported in Annala & Poutanen (2010), spectroscopic information on Ae/Be stars is given in Fairlamb et al (2015), tabled data on BeHMXBs is presented in Tsygankov et al (2017) and Reig et al (2017), HMXBs detected by INTEGRAL are reported in , an overview of SFXT candidates is given in Sguera et al (2020), much information on radio pulsars is collected in van den Eijnden et al ( 2021), XMM-Newton and Swift A&A proofs: manuscript no. aa45236 observations of sgHMXBs are reported in Ferrigno et al (2022), and HMXBs seen by Fermi are presented in Harvey et al (2022).…”
Section: Retrieving Binary Parameters and New Hmxbsmentioning
confidence: 99%
“…There are also more than 160 confirmed and candidate Be X-ray binaries (BeXRBs; Raguzova & Popov 2005), 12 which are mostly Be+NS systems that probably evolved in a similar fashion as the Be+sdO binaries but from more massive progenitor systems (Reig 2011). The Be primaries occupy a narrow range between O9 and B2 in spectral type (Reig et al 2017). These systems are conspicuous due to the X-ray emission resulting from the (episodic) accretion of Be disk material onto the compact object, so that the sample is drawn from a much larger (partly extragalactic) volume.…”
Section: Introductionmentioning
confidence: 99%